Effect of plasma treatment on hydrophobicity and barrier property of polylactic acid - C. Chaiwong (2018)
In this work, we investigated the influence of SF6 plasma generated by an inductively coupled discharge on the hydrophobicity and barrier properties of poly(lactic acid), PLA. It was found that SF6 plasma enhanced the hydrophobicity of PLA as observed in the increase of the water contact angle. Water absorption time of the plasma-treated PLA was two-fold increased. However, the plasma treatment did not have significant influence on water vapor permeability of PLA. The differential scanning calorimetry results revealed that the bulk structure which controls transportation property of PLA remained unchanged after plasma treatment. Atomic force microscopy showed topographical modification after plasma treatment. Attenuated total reflectance Fourier transform infrared spectroscopy and x-ray photoelectron spectroscopy showed the bounding of fluorines in the PLA structure, which leads to the increase in hydrophobicity of PLA. © 2010 Elsevier B.V.